Gender and Chinese Translations of Chinese American Women's Literature: Marital Sexual Violence in Amy Tan's The Kitchen God's Wife. (September 2021) - Tang, Beibei
Abstract : Comparing three Chinese translations of Amy Tan's novel The Kitchen God's Wife (1991), this article explores gender issues in Chinese translations of Chinese American women's literature from a feminist perspective. Using the feminist concept of female alienation, it explores how feminist consciousness and sexual alienation caused by marital sexual violence in the source text are expressed in the Chinese translations, and how far the translations achieve (feminist) translation equivalence. Special attention is paid to the translators' gender consciousness and ideologies, as reflected in their translations, in order to explore the role played by gender in the translation of women's writing.